Isolation and characterization of Trichoderma erinaceum for antagonistic activity against plant pathogenic fungi. - Herath, H.H.M.A.U.; Wijesundera, R.L.C.; Chandrasekharan, N.V.; Wijesundera, W.S.S.; Kathriarachchi, Hashendra (My University, 2015)
Trichoderma is reported to be one of the most widely distributed soil fungi and the biocontrol potential of Trichoderma has been studied against a wide range of plant pathogenic fungi. In the present study T. erinaceum was screened for antifungal activity against seven selected plant pathogenic fungi and for chitinase and glucanase production. In antifungal assays highest mean percent inhibition was observed against the pathogenic fungus Rhizoctonia solani (72.66 % ±7.6). Molecular characterization of rDNA of ITS region was made for identification and it was identified as Trichoderma erinaceum.
Keywords: biocontrol – chitinase – glucanase – ITS